Review of Maritime Transport 2017 - United Nations Conference on Trade; Development (United Nations, 2017)
With over 80 per cent of global trade by volume and more than 70 per cent of its value being carried on board ships and handled by seaports worldwide, the importance of maritime transport for trade and development cannot be overemphasized. The 2017 Review of Maritime Transport presents and discusses key developments in the world economy and international trade and related impacts on shipping demand and supply, freight and charter markets, as well as seaports and the regulatory and legal framework. In addition to relevant developments in 2016 and the first half of 2017, this year’s edition of the Review also features a special chapter on maritime transport connectivity, reflecting the prominence of physical and electronic connectivity as a priority area in the trade and development policy agenda.